2019
DOI: 10.1159/000496537
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Older Adults with Mild Dementia: Dementia with Lewy Bodies and Alzheimer’s Disease

Abstract: Introduction: The aim of the study is to describe the frequency of frailty in people with a new diagnosis of mild dementia due to Alzheimer’s disease (AD) and dementia with Lewy bodies (DLB). Methods: This is a secondary analysis of the Dementia Study of Western Norway (Demvest). For this study, we analysed a sample of 186 patients, 116 with AD and 70 with DLB. Subjects were included at a time in which mild dementia was diagnosed according to consensus criteria after comprehensive standardized assessment. Frai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
5
29
0
1
Order By: Relevance
“…We have shown that attention is associated with ADL in PDD, 38 as well as sleep disorders and parkinsonism. 13,39 The association between longitudinally assessed NPSs and functional trajectory is in line with the previously evidenced unstable course of NPSs observed in both AD and LDB, 8 and underline why regularly and structured assessments of NPSs are important. Current data imply that both prevention and treatment of NPSs may be beneficial also with regard to functional decline.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We have shown that attention is associated with ADL in PDD, 38 as well as sleep disorders and parkinsonism. 13,39 The association between longitudinally assessed NPSs and functional trajectory is in line with the previously evidenced unstable course of NPSs observed in both AD and LDB, 8 and underline why regularly and structured assessments of NPSs are important. Current data imply that both prevention and treatment of NPSs may be beneficial also with regard to functional decline.…”
Section: Discussionsupporting
confidence: 83%
“…[10][11][12] In people living with LBD, NPSs, comorbidity, frailty, and functional impairment are more frequent and severe than for people with AD. 8,13,14 These characteristics make this group more prone to dependency and to a worse prognosis when compared with other common dementias. 13,14 Little is known regarding the impact of the total NPS burden on the functional trajectories in people living with dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty is a common clinical syndrome in older adults due to age-related cumulative decline in multiple physiological systems, associated with negative health outcomes, including deterioration of daily living activities, disability, institutionalization, morbidity, and mortality (1). Cross-sectional and longitudinal research has demonstrated that older adults with physical frailty exhibit poorer cognitive performance and greater risk of cognitive decline and dementia than individuals without frailty (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and that individuals with cognitive decline or dementia show a higher risk of physical frailty (16)(17)(18). It has also been demonstrated that the coexistence of physical frailty and cognitive impairment (cognitive frailty), ranging from 1 to 5% in community-dwelling older adults (19), increases the risk of mortality (20)(21)(22)(23)(24)(25), functional disability (26), and incident neurocognitive disorders (9,27) in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Презентація психопатологічної симптоматики різниться залежно від типів деменції, а частота презентації подібної симптоматики може змінюватись залежно від стадій деменції. На ранніх стадіях хвороби, зокрема, переважають депресія, дезінгібіція, апатія та порушення сну, а прогресування хвороби призводить до збільшення частоти появи психопатологічних симптомів, як-от марення, галюцинацій та агресії [3][4][5]. При судинній деменції розлади сну, збудження, депресія та тривожність не пов'язані з конкретною стадією захворювання [6].…”
unclassified